Critical Capabilities of Corporate Information Systems - Darius Antoni (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Institut Teknologi Sumatera, Lampung Selatan, Lampung, Indonesia, 2018)
Abstract—this paper aims to identify the critical factors for evaluating the capabilities of corporate information system in Palembang from the perspective of the IT infrastructure and IT human resources competence. To fulfill these objectives of the study, this study adopts a conceptual framework that is developed by Antoni and Jie (2012). The framework consists of IT infrastructure quality and competence of IT human Resources, which are used as foundation of business operations in organizations. There is a need to develop their capabilities through the adoption of IT to enhance its performance and enhance their competitive position in the market place. IT capability is an organizational ability in effectively and efficiently using their IT resources, which can be determined by IT infrastructure, and IT human resource competencies. Findings indicate that there are many the critical capabilities of IT infrastructure and IT human Resource capabilities that can be utilized by organizations to develop their competencies in order to improve business performance. In Addition, the findings of the study would be of practical significance to the continuous improvement of organizational performance in Palembang and other cities in Indonesia.